ANALISIS PERUBAHAN FASIES DAN LINGKUNGAN PENGENDAPAN DI BLOK A PADA FORMASI MELUHU, CEKUNGAN KENDARI, PROVINSI SULAWESI TENGGARA - Irfansyah, Febry; Nugroho, Hadi; Aribowo, Yoga (Geological Engineering E-Journal, 2013)
Limitations of field geological data and subsurface surveys are one of the causes of unattractiveness oil and gas exploration activities in the old basins in eastern Indonesia because it has a high risk that is always avoided by investors in the oil and gas. The research location in Meluhu Formation, Kendari Basin, which is one of Upper Triassic formations in eastern Indonesia is estimated to have potential for hydrocarbon resources. Therefore, to find out more about this potential is conducted by field geological survey that generate data on sedimentology and stratigraphy. This study aims to determine facies and depositional environment that formed in three tracks of stratigraphic section in Block A, Meluhu Formation, Kendari Basin, and to know the changes in facies and depositional environment vertically associated with the impact of sea level changes. The methodology used in this research is descriptive and analysis methods. The descriptive method is done by literature study and field survey includes stratigraphic section measurements at selected tracks, while for analysis methods are litofasies analysis, facies associations, petrographic analysis, and sequence analysis of the relative age. Based on the four analysis, a stratigraphic column of the study area that are arranged based on the relative age of rocks are made and used to determine the pattern of changes in facies and depositional environment vertically. From the combined results of the four methods of analysis, the interpretation of different facies and depositional environment in three stratigraphic section measurements in this area are obtained. On the first track named LS301, some facies found, such as mud flats, mixed flats, sand flats, and tidal channel, which characterize the tidal flat depositional environment. In the second track named LS303, channel fills and overbank facies are found, which characterize the fluvial depositional environment. On the third track named LS306, facies mud flats and sand flats that characterize the deposition of tidal flats are found, and the dominance of overbank and channel fill facies that characterize the fluvial depositional environment. From the analysis of the relative age, the sequence between tracks from old to young is LS301, LS303, and the LS306. So, changes in facies and depositional environment vertically starts from tidal flat and change into fluvial. Compared with the eustacy curve of the Upper Triassic age by Haq (1987) which shows a pattern of decline in sea level, vertical changes on Block A match to the facts on the field.